2021
DOI: 10.1002/tea.21685
|View full text |Cite
|
Sign up to set email alerts
|

Examining student environmental science agency across school science contexts

Abstract: To address the limited time and support for elementary science, science instruction is sometimes distributed among classroom teachers, science specialists, and informal science educators, creating a complex school science culture. We investigate how student agency may be enabled and constrained when school science learning happens simultaneously across multiple school contexts. Using a social practice theory lens, we examine how three third‐grade students with a strong interest in science attempt to pursue the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…According to the teachers, however, it is confirmed that students took on specific roles and recognized themselves as experts, both in running their business and in promoting the cultural heritage. This draws upon previous research that reveals that primary school is an appropriate level to invest in such change (Harris & Ballard, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…According to the teachers, however, it is confirmed that students took on specific roles and recognized themselves as experts, both in running their business and in promoting the cultural heritage. This draws upon previous research that reveals that primary school is an appropriate level to invest in such change (Harris & Ballard, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The Meadian perspective conceptualizes identity as ever-changing as one navigates the social roles, positions, and interactions in everyday practices (Mead, 1934). Specifically, a social practice theory (SPT) of identity was used to guide this research, as it is the theoretical framework of numerous science identity studies (Barton & Tan, 2010;Carlone et al, 2015;Carlone & Johnson, 2007;Riedinger & McGinnis, 2017), environmental identity studies within an educational context (Blatt, 2013(Blatt, , 2014Simms & Shanahan, 2019;Stapleton, 2015;Williams & Chawla, 2016) and research at the intersection of school science and citizen science (Harris & Ballard, 2021).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Some studies investigated the effects of CS beyond traditional learning outcomes and focused on the development of (environmental) science agency and STEM identity. Those studies reported evidence for agency development in informal and formal settings (Ballard et al, 2017;Harris & Ballard, 2021) as well as for the development of scientific citizenship (Wallace & Bodzin, 2017). Further, Maass et al (2022) discuss how modelling real-life problems relevant to society, an activity that is essential in many CS projects (e.g.…”
Section: Citizen Science Learning Outcomes In Studentsmentioning
confidence: 99%
“…Although some studies focused on CS in formal education settings (e.g. Castagneyrol et al, 2020;Harris & Ballard, 2021;Kelemen-Finan et al, 2018;Wallace & Bodzin, 2017), most studies examined the effects on students and only very few focused on teachers. Scheuch et al (2018) were able to show that, when participating in CS with their students, "teachers managed to combine project and curriculum goals concerning environmental education" and successfully supported their students in appreciating biodiversity (p. 86).…”
Section: Effects Of Citizen Science Participation On Teachersmentioning
confidence: 99%